Hope or dismay: An ethnography of reverse migration trends in Alberta, Canada - Majid Hussain Alias Ghalib Hussain; Hania Iman; Sadia Khanum (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Alberta’s identity as an attractive province for migrants is shifting as an increasing number of migrants choose to leave the province amid crises and changing perceptions of opportunity. For some, reverse migration represents hope for stability; for others, it mirrors dismay over disappointments and declining livelihoods. This study explores reverse migration trends, whether based on hope for a better future or dismay owing to various factors. These research was conducted among Muslim migrants from Alberta, Canada. Data for this study were collected using ethnographic research methods in Alberta from June 2024 to October 2024. Data collection tools and techniques included participant observation, in-depth interviews, and conversational interviews. Responses were obtained from 20 informants. The findings revealed that reverse migration is not necessarily towards the home country only; rather, many Muslim immigrants have chosen other countries as their next homes. This study concludes that several factors, including economic, political, social, and environmental factors, as well as quality of life, and pull factors such as cultural familiarity, sense of belonging, identity, and family connections, are the driving factors in promoting immigrants’ decisions to leave Canada.